Between Development and Marginalization: Relocating the Craftsmanship from the Old Medina of Fez to the Peripheral Neighborhood of Ain Nokbi - Hanzaz, Imane; Harroud, Tarik (Advances in Social Sciences Research Journal, 2025)
Craftsmanship constitutes a key component of the Medina of Fez in Morocco, which is considered as the oldest and the largest Medina in the world. Supported by the American fund of Millennium Challenge Corporation, the Artisanat Fez Medina project was envisioned as a sustainable response to multiple challenges in the Medina of Fez : reducing pollution related to some handicraft activities such as brassware, improving working conditions for artisans, preserving the heritage and developing the attractivity of the Medina. The project aimed to renovate the Lalla Yeddouna Square as the heartbeat of the historic fabric of Fez, where brass craftsmen were working under unsanitary conditions and participating in the pollution of the main river of Fez, Oued Boukhrareb, by discharging heavy metals and toxins. Also, the project has relocated brass artisans far from the Lalla Yeddouna Square, to the peripheral and industrial zone Ain Nokbi. This paper analyses through semi-structured interviews how this new scheme has raised critical questions regarding the resilience of artisans, and the vulnerabilities produced in terms of spatial integration, economic precarity, and cultural displacement.